Mediastinal hemangioma presenting with a characteristic feature on dynamic computed tomography images - Li, Sheng-Min; Hsu, Hsian-He; Lee, Shih-Chun; Gao, Hong-Wei; Ko, Kai-Hsiung (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
emangiomas are uncommon benign tumors of the mediastinum. The definite diagnosis is sometimes difficult to make because of usually nonspecific features on single-phase contrast-enhanced computed tomography (CT) images. We described a 60-year-old woman suffering from a neck mass with progressive enlargement. On the dynamic CT study, the tumor showed peripheral nodular enhancement on early phase images and progressive centripetal fill-in on delayed phase images. Hemangioma was preoperatively diagnosed on the basis of this characteristic CT appearance.